Severe acute respiratory syndrome and the innate immune responses: modulation of effector cell function without productive infection - Tseng, Chien-Te K; Perrone, Lucy A; Zhu, Hongbing; Makino, Shinji; Peters, Clarence J (The Journal of immunology (1950), 2005)
Severe acute respiratory syndrome (SARS) caused by a novel human coronavirus (CoV), designated SARS-CoV, is a highly contagious respiratory disease with the lungs as a major target. Although the exact mechanism of SARS-CoV pathogenesis remains unknown, an intense, ill-regulated local inflammatory response has been suggested as partially responsible for the devastating lung pathology. We investigated the interaction of SARS-CoV with human macrophages (Mphi) and dendritic cells (DC), two key innate immune cells of the host immune system, by focusing on their susceptibility to viral infection and subsequent responses (e.g., phenotypic maturation, T cell-priming activity, phagocytosis, and cytokine production). We found neither cell to be permissive for SARS-CoV replication. However, incubation of Mphi and DC with live, but not gamma irradiation-inactivated, viruses appeared to better sustain their viability. Also, exposure to infectious SARS-CoV led to the phenotypic and functional maturation of DC, with regard to MHC class II and costimulatory molecule expression, T cell-stimulatory capacity, and cytokine production, respectively. Cytokine production was also observed for Mphi, which were refractory to cell surface phenotypic changes. Strikingly, live SARS-CoV could further prime cell types to respond to a suboptimal dose of bacterial LPS (100 ng/ml), resulting in massive release of IL-6 and IL-12. However, the endocytic capacity (e.g., Ag capture) of Mphi was significantly compromised upon exposure to infectious SARS-CoV. This study is the first demonstration that although SARS-CoV does not productively infect human Mphi or DC, it appears to exert differential effects on Mphi and DC maturation and functions, which might contribute to SARS pathogenesis.